A groundwater security model based on hydraulic turnover times and flow compartments - Pacheco, Fernando António Leal; de Melo, Marília Carvalho; Pissarra, Teresa Cristina Tarlé [UNESP]; Álvarez, Xana; Martins, Lisa Maria de Oliveira; Fernandes, António Carlos Pinheiro; Moura, João Paulo; Fernandes, Luís Filipe Sanches (Elsevier, 2022)
Starting with a log-linear relationship between groundwater discharge per unit drainage area (Q/Ab), hydraulic turnover time (t) and aquifer mobile storage (z), this study builds a groundwater security method at catchment scale. The method embeds previously published approaches to calculate Q/Ab, t and z, and relies solely on stream flow discharges and watershed areas. The ability to build a method on a couple of variables is remarkable. The method recasts the calculated variables as aquifer security indicators (SQ, St and Sz), relating SQ with yield capacity, St with self-depuration capacity and Sz with resilience. Groundwater security is the weighted product of SQ, St and Sz. The method is validated with stream flow discharges and drainage areas concerning 294 hydrometric stations and their watersheds, located in continental Portugal. The results revealed a majority of moderately to highly secure watersheds, especially as regards St (> 62%), while 7–10% were classified as very highly secured in general (SQ-St-Sz). The least secured basins are located in the more arid regions of continental Portugal (Northeast and south regions), as expected. The method can be easily transposed to any other region worldwide, with the necessary adaptions to regional climate, geological and topographic settings. • Compile stream flow discharge data and organize them as natural logarithms and logarithmic variations as function of time, to estimate Q, t and z; • Recast the Q, t and z values as SQ, St and Sz ratings, respectively, using the appropriate reclassification scales, and estimate watershed security levels, namely average security or customized (weighted) securities that highlight the contributions of Q/Ab (watershed yield), t (aquifer's self-depuration capacity) or z (aquifer's resilience); • Use the results to draw illustrative diagrams and spatial distribution maps.
Keywords: A groundwater security model based on hydraulic turnover times and flow compartments; Aquifer resilience; Aquifer self-depuration capacity; Aquifer yield capacity; Groundwater discharge; Hydraulic turnover time; Sustainable water supply; Watershed mobile storage